Preliminary observations on dominance of crustacean larvae in the diet of little tunny Euthynnus affinis (Cantor, 1849) caught off Chennai and Cuddalore coasts - Suresh Gupta, K.; Kizhakudan, Shoba Joe; K. Kizhakudan, Joe; Yousuf, K.S.S.M.; Raja, S. (Indian Journal of Fisheries, 2014)
The food habits of little tunny Euthynnus affinis caught by hooks and line off Chennai and Cuddalore in Tamil Nadu were studied from December 2011 to August 2012. A total of 358 samples were collected from both the centres and gut contents were analysed. Almost 42% of the guts were full and 22% were found to be either quarter full or with traces of food contents. About 35% of the guts were empty. Index of relative importance (IRI) was calculated for the prey items. Crustacean larvae (91%) were dominant among the gut contents, followed by fishes (4%) and molluscs (2%). Among the crustacean larvae, brachyuran megalopae and crablets formed about 45% while the stomatopod alima larvae formed 21%. Phyllosoma larvae of scyllarid lobsters and pueruli larvae of spiny lobsters were also found among the identified crustacean larvae.